Loss of Ethanolamine Utilization in Enterococcus faecalis Increases Gastrointestinal Tract Colonization - Karan Gautam Kaval (American Society for Microbiology, 2018)
ABSTRACT Enterococcus faecalis is paradoxically a dangerous nosocomial pathogen and a normal constituent of the human gut microbiome, an environment rich in ethanolamine. E. faecalis carries the eut (ethanolamine utilization) genes, which enable the catabolism of ethanolamine (EA) as a valuable source of carbon and/or nitrogen. EA catabolism was previously shown to contribute to the colonization and growth of enteric pathogens, such as Salmonella enterica serovar Typhimurium and enterohemorrhagic Escherichia coli (EHEC), in the gut environment. We tested the ability of eut mutants of E. faecalis to colonize the gut using a murine model of gastrointestinal (GI) tract competition and report the surprising observation that these mutants outcompete the wild-type strain. IMPORTANCE Some bacteria that are normal, harmless colonizers of the human body can cause disease in immunocompromised patients, particularly those that have been heavily treated with antibiotics. Therefore, it is important to understand the factors that promote or negate these organisms’ ability to colonize. Previously, ethanolamine, found in high concentrations in the GI tract, was shown to promote the colonization and growth of bacteria associated with food poisoning. Here, we report the surprising, opposite effect of ethanolamine utilization on the commensal colonizer E. faecalis, namely, that loss of this metabolic capacity made it a better colonizer.